2018
DOI: 10.1021/acs.jafc.7b03285
|View full text |Cite
|
Sign up to set email alerts
|

Urolithins Attenuate LPS-Induced Neuroinflammation in BV2Microglia via MAPK, Akt, and NF-κB Signaling Pathways

Abstract: Emerging data suggest that urolithins, gut microbiota metabolites of ellagitannins, contribute toward multiple health benefits attributed to ellagitannin-rich foods, including walnuts, red raspberry, strawberry, and pomegranate. However, there is limited data on whether the potential neuroprotective effects of these ellagitannin-rich foods are mediated by urolithins. Herein, we evaluated the potential mechanisms of antineuroinflammatory effects of urolithins (urolithins A, B, and C; 8-methyl-O-urolithin A; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(100 citation statements)
references
References 47 publications
6
93
0
1
Order By: Relevance
“…A recent study demonstrated that the Liraglutide (GLP-1 agonist) ameliorates cartilage degeneration in a rat model of knee osteoarthritis with anti-inflammatory activity [32]. Valproic acid and butyrate were widely reported as latent therapeutic agents for OA due to their ability to suppress IL-1β-induced inflammation and cartilage degradation [33,34]. During disease progression, IL-1β stimulates the expression of the matrix metalloproteinase (MMPs) that mediate the degradation of cartilage matrix components and suppress proteoglycan synthesis [35].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that the Liraglutide (GLP-1 agonist) ameliorates cartilage degeneration in a rat model of knee osteoarthritis with anti-inflammatory activity [32]. Valproic acid and butyrate were widely reported as latent therapeutic agents for OA due to their ability to suppress IL-1β-induced inflammation and cartilage degradation [33,34]. During disease progression, IL-1β stimulates the expression of the matrix metalloproteinase (MMPs) that mediate the degradation of cartilage matrix components and suppress proteoglycan synthesis [35].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the catabolites derived from the ellagitannin, such as urolithins and pyrogallol, are effective antiglycating as well as antioxidant agents [45]. Urolithins were also shown to attenuate the neuroinflammation in BV2 microglia by various other mechanisms, including the NF-κB, MAPK and Akt signaling pathways [60]. Urolithins, such as those derived from pomegranates, act as neuroprotectors and can potentially prevent the AD.…”
Section: Polyphenols As Antiglycating Agentsmentioning
confidence: 99%
“…Vanillin (4‐hydroxy‐3‐methoxybenzaldehyde) (VA), a kind of phenolic compound, is a major component of Vanilla planifolia seed (Sinha, Sharma, & Sharma, ; Xu et al., ) and widely found in food and beverage (as shown in Supporting Information Table S1), such as biscuit (9.3 to 42.6 µg/g), candy (36.7 to 2860.0 µg/g), milk powder (132.9 to 1990.0 µg/g), and Baijiu (210 to 306 µg/L) (Deng, Xu, Zeng, & Ding, ; Ni, Zhang, & Kokot, ; Zhao et al., ; Ziyatdinova, Kozlova, Ziganshina, & Budnikov, ). In Gujinggong Baijiu (a well‐known brand of strong‐aroma type Baijiu), VA was identified as a contributor for the aroma profile due to its higher flavor dilution value (≥729) (Liu & Sun, ; Zhao et al., ).…”
Section: Introductionmentioning
confidence: 99%